Sharing budgetary austerity under free mobility and asymmetric information : an optimal regulation approach to fiscal federalism - Marie-Laure Breuille; Robert J. Gary-Bobo (Center for Economic Studies and ifo Institute (CESifo), 2005)
In the present article, Tiebout meets Laffont and Tirole in the land of Fiscal Federalism. We use a non-trivial Principal-Multi-Agent model to characterize the optimal intergovernmental grant schedule, when the cost of local public goods depends on hidden characteristics and actions of local governments, and under citizen free mobility. We show that local governments earn informational rents, and how optimal local taxes, public good production levels and land prices are jointly distorted at the second-best optimum, as a consequence of free mobility and asymmetric information. The effect of informational asymmetries is to decrease the average production of public goods and to increase the inter-jurisdictional variance of taxes and public-good production.
Keywords: D72; H7; D82; 330; asymmetric information; Principal-Agent model; public budget deficits; freemobility equilibrium; fiscal federalism; Finanzausgleich; Finanzföderalismus; Agency Theory; Asymmetrische Information; Öffentliches Gut; Binnenwanderung; Abwanderung und Widerspruch; Theorie